2006
DOI: 10.1017/s1049096506060471
|View full text |Cite
|
Sign up to set email alerts
|

The Limits of Political Efficacy: Educating Citizens for a Democratic Society

Abstract: You can try and change things, but basically it will just make you feel bad for trying. They didn't even want to hear what I was saying. They don't care."-Justin, a high school senior, when asked about the semester he spent working to improve his community

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
139
0
11

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(170 citation statements)
references
References 11 publications
4
139
0
11
Order By: Relevance
“…Accordingly, community service and service-learning have been positively associated with the subsequent importance assigned to helping other people (Serow 1991;Scales et al 2000;Kahne and Westheimer 2006), community involvement (Johnson et al 1998;Kahne and Sporte 2008), and such moral values as being just and caring (Yates and Youniss 1996). However, other studies have revealed null or mixed findings (e.g., Melchior 1999;Raskoff and Sundeen 1999;Pratt et al 2003;Cemalcilar 2009).…”
Section: Community Service and The Formation Of A Prosocial Value Orimentioning
confidence: 99%
“…Accordingly, community service and service-learning have been positively associated with the subsequent importance assigned to helping other people (Serow 1991;Scales et al 2000;Kahne and Westheimer 2006), community involvement (Johnson et al 1998;Kahne and Sporte 2008), and such moral values as being just and caring (Yates and Youniss 1996). However, other studies have revealed null or mixed findings (e.g., Melchior 1999;Raskoff and Sundeen 1999;Pratt et al 2003;Cemalcilar 2009).…”
Section: Community Service and The Formation Of A Prosocial Value Orimentioning
confidence: 99%
“…As one Pro-Vice-Chancellor remarked, the theory is that by providing volunteering opportunities this will engender students' awareness of their responsibilities, yet in practice there is less evidence of how this may be achieved (Kahne and Westheimer, 2006).…”
mentioning
confidence: 99%
“…If we assume that the participation in EPS might decrease students' trust and increase their cynicism, then it could be argued that the youth councils would not encourage children to become (or remain) uncritical compliant subjects (Adu-Gyamfi, 2013;Raby, 2012). Instead, if we, like Kahne and Westheimer (2002) and like some of our participants, understand that low levels of trust in politics can be explained by a critical analysis of politics, we could wonder whether the councils actually encourage critical analysis of how politics is currently conducted. Similar analyses can be applied to our data looking at anticipated participation.…”
Section: Discussionmentioning
confidence: 99%